Incentivizing organ donation through a nonmonetary posthumous award. (20th August 2019) - Bedendo, Mascia; Siming, Linus
Abstract: Since 2013, The Order of St John Award for Organ Donation has been offered to the families of deceased solid organ donors in the United Kingdom to honor the donors and inspire others to donate. We evaluate the effects of this award using a difference‐in‐differences approach that builds on the fact that solid organ donors are eligible for the award, whereas cornea‐only donors are not. We find that the introduction of the award led to an increase in the number of deceased solid organ donors.